PENGARUH PENERAPAN COOPERATIVE LEARNING TIPETHE POWER OF TWO AND FOUR TERHADAP PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VII SMPN 22 PADANG - Rahmi, Rahmi; Saputri, Vina Delfia (Prodi Pendidikan Matematika, 2013)
TheÂ purposeÂ ofÂ thisÂ researchÂ isÂ toÂ knowÂ whetherÂ studentsâÂ understandingÂ of mathematics concept by using Cooperative Learning of The Power of two and Four typeÂ isÂ isÂ betterÂ thanÂ studentsâÂ understandingÂ ofÂ mathematicsÂ conceptÂ byÂ using conventionalÂ methodÂ forÂ studentÂ garadeÂ VIIÂ ofÂ SMPNÂ 22Â Padang.Â TheÂ kindÂ of Â this research is experimental research. The sample of this research is student in class VII 6 and VII 7. The instrument of this research is final test in essay form which consists of Â indicator of concept understanding. The reliability of the test is0.71.Based on the data analysis, it is found that the meanscore of the test related toÂ studentsâ understanding of mathematics concept in experimental class isÂ 77.31 and it is higher than control class that is 69.59. Hypothesis testing by using t-test found that p-value 0.015 is lower than Î±= 0,05. It can be concluded that studentsâ understandingÂ of mathematics concept by using Cooperative Learning of The Power of Two and FourÂ typeÂ isÂ betterÂ thanÂ studentsâÂ understandingÂ ofÂ mathematicsÂ conceptÂ byÂ using conventional method.